Proceedings of the Graduate Research in Education Seminar (GREduc) 2018 - Faculty of Educational Studies (Faculty of Educational Studies, 2018)
The Graduate Research in Education (GREDuc) 2018 Seminar, held on December 15, 2018, and organized by the Faculty of Educational Studies, Universiti Putra Malaysia, focused on the theme Revolutionalising Research Practices in Education and Human Resource Development